2022
DOI: 10.3389/fonc.2022.870570
|View full text |Cite
|
Sign up to set email alerts
|

Four-Dimensional Image-Guided Adaptive Brachytherapy for Cervical Cancer: A Systematic Review and Meta-Regression Analysis

Abstract: PurposeThe ICRU/GEC-ESTRO released the ICRU Report No. 89, which introduced the concept of four-dimensional brachytherapy and ushered in a new era of brachytherapy for cervical cancer. The purpose of this study was to evaluate the local control and late toxicity of four-dimensional brachytherapy in cervical cancer through a systematic review and to reveal the dose-response relationship between the volumetric dose paraments and the local control rate via a probit model.Material and MethodsWe identified studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Secondly, the total number of patients included in the probit analysis was not high due to the relative rarity of vaginal cancer, and they were all observational studies. Finally, the heterogeneity of the data remains an important limitation of this study, as previously stated [ 22 24 ].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Secondly, the total number of patients included in the probit analysis was not high due to the relative rarity of vaginal cancer, and they were all observational studies. Finally, the heterogeneity of the data remains an important limitation of this study, as previously stated [ 22 24 ].…”
Section: Discussionmentioning
confidence: 85%
“…For cervical cancer, we have previously analyzed the dose-response relationships in image-guided BT [ 22 ], three-dimensional intracavitary combined with interstitial BT [ 23 ], and four-dimensional adaptive BT [ 24 ], and obtained results consistent with current consensus of dose constraints [ 25 ]. The purpose of this study is to identify articles that reported volume base dose and local control in definitive radiotherapy for vaginal cancer through systematic literature screening, and to conduct probit model analysis in an attempt to find the optimal dose for definitive radiotherapy for vaginal cancer.…”
Section: Introductionmentioning
confidence: 96%
“…Over the past two decades, advancements in imaging technologies have enabled new methods of guidance for brachytherapy. The initial steps were made with CT-guided brachytherapy [ 12 ] and later with MRI-guided brachytherapy [ 8 , 9 , 13 , 14 ]. Over time, two-dimensional, point-A-based planning was replaced by three-dimensional, adaptive planning.…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, several advances in brachytherapy technique have led to improved cure rates and reduced toxicity, notably the implementation of magnetic resonance imaging (MRI) before and during brachytherapy application, as well as the adoption of adaptive, three-dimensional planning [ 7 , 8 , 9 ]. Today cure rates remain high with negative pelvic lymphadenopathy, gross tumor volume (GTV) dose covering 90% of the target (GTV D90) of >110 Gy, and a treatment duration of ≤56 days predictive of better outcomes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probit model regression analysis was conducted by XLSTAT 2016 (Addinsoft, Paris, France) as previously described [ 11 , 12 ]. The statistical significance was set at the level of P value < 0.05.…”
Section: Methodsmentioning
confidence: 99%